VIBRATIONAL STRUCTURE OF EXCITED-STATES OF MOLECULES ON OXIDE SURFACES - Libuda, Jörg; et al. (ELSEVIER SCIENCE BV, 1993)
A more detailed knowledge of excited states of molecules adsorbed on solid surfaces is interesting from various points of view. To understand, for example, photochemistry at surfaces, the lifetimes of excited states are important parameters.We report ELS spectra showing vibrational structure for CO on a thin (thickness: 5 Angstrom) gamma-Al2O3(111) film grown on a NiAl(110) surface. The molecules desorb from the surface in the range 35 K < T < 75 K and thermal desorption spectroscopy (TDS) allows us to differentiate between monolayer and multilayer regimes. Two species exist in the monolayer. From the observed line widths of the vibrational sub-bands in electron energy loss spectroscopy (ELS) life times are estimated. For Oz on the same surface, TDS also indicates the presence of monolayer and multilayer adsorption. With ELS, sharp signals from two excited states, known from the gas phase to be spin flip excitations, are observed. This indicates that there is no strong spin coupling between the O-2 molecules and the metal substrate underneath the oxide film. Angle resolved ELS data reveal no pronounced angle dependent cross section effects.